A comparison of the effects of oral vs. intravenous hydration on subclinical acute kidney injury in living kidney donors: a protocol of a randomised controlled trial. Issue 1 (December 2017) - Mackinnon, Shona; Aitken, Emma; Ghita, Ryan; Clancy, Marc
Abstract Background Optimal treatment for established renal failure is living donor kidney transplantation. However this pathway exposes healthy individuals to significant reduction in nephron mass via major surgical procedure. Laparoscopic donor nephrectomy is now the most common method for live donor transplantation, reducing both donor post-operative pain and recovery time. However this procedure exposes kidneys to additional haemodynamic stresses. It has been suggested that donor hydration—particularly the use of preoperative intravenous fluids—may counteract these stresses, reducing subclinical acute kidney injury and ultimately improving long-term renal function. This may be important in both preservation of donor renal function and recipient graft longevity. Methods/Design A prospective single-centre single-blinded randomized controlled trial will be carried out to determine the effects of donor preoperative intravenous fluids. The primary outcome is donor subclinical acute kidney injury (defined as plasma NGAL, >153 ng/ml) on day 1 postoperatively. Secondary outcomes include intraoperative haemodynamics, recipient subclinical acute kidney injury, perioperative complications and donor sleep quality. Donors will be randomised into two groups: the intervention group will receive active pre-hydration consisting of three litres of intravenous Hartmann's solution between midnight and 8 am before morning kidney donation, while the control group will not receive this. Both groups will receive unlimited oral fluids until midnight, as is routine. Plasma NGAL will be measured at pre-specified perioperative time points, intraoperative haemodynamic data will be collected using non-invasive cardiac output monitoring and clinical notes will be used to obtain demographic and clinical data. The researcher will be blinded to the donor fluid hydration status. Blinded statistical analysis will be performed on an intention-to-treat basis. A prospective power calculation estimates a required sample size of 86 patients. Discussion This study will provide important data, as there is currently little evidence about the use of donor preoperative fluids in laparoscopic nephrectomy. It is hoped that the results obtained will guide future clinical practice. Trial registration This study has been approved by the West of Scotland Research Ethics Committee 3 (reference no. 14/WS/1160, 27 January 2015) and is registered with the International Standard Randomised Controlled Trial Number Register (reference no.ISRCTN10199225, 20 April 2015).